RANCANG BANGUN INTEGRASI APLIKASI PUBLIC ADDRESS SYSTEM TEXT TO SPEECH DAN FLIGHT INFORMATION DISPLAY SYSTEM BERBASIS WIRELESS GUNA MENINGKATKAN KUALITAS PELAYANAN JASA INFORMASI DI BANDAR UDARA HALIM PERDANA KUSUM - Daniel Merkuri Lengkong; Muhammad Wildan; Toni (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
The design of this application program is intended to facilitate users of flight services at airports to obtain information contents in a variety of languages (Indonesian, English, Chinese, Arabic) without any misinterpretation of meaning caused by intonation or accent lacking information officers true, besides that it is also to ease the workload of information officers in carrying out their work in operating or using Public Address System (PAS) and Flight Information Display System (FIDS) as a tool that serves to provide flight information to flight service users.